Heat demand for heating apartment buildings/Gyvenamųjų namų faktinio šiluminės energijos poreikio sulyginimas su projektine šildymo sistemų galia - Karbauskaitė, Jūratė; Stankevičius, Vytautas (Journal of Civil Engineering and Management, 2000)
In this paper the results of statistic analysis of heat consumption in apartment heating systems for Lithuania are discussed. Kaunas district heating system data are used for the analysis. Total sum of buildings involved is about 1900, including 1550 with the average heated area of 4000 m2. It has been established that real heat consumption in apartment buildings is less than the design heat demand (Fig 1), especially in small buildings (Fig 2). The distribution of monthly differences is presented in Fig 3. The difference during months does not depend on average outdoor temperature, but it could be caused by temperature fluctuations and solar radiation. It is quite important to determine the reasons of different heat consumption in buildings. For this purpose 20 dwelling houses of various design and building period, with various energy consumption problems have been selected for more detailed energy audit. Volumes of external building elements, changes in destination of premises, heated area have been estimated as well as the state of heat supply sub-station equipment. According to the data obtained, the energy consumption was determined for standard month at mean indoor and outdoor climate values. The results are compared with real energy consumption in the selected buildings and design values. It has been established that the inadequacies in exceeded energy consumption over design values are mostly caused by incorrect heated area registration and premises destination change, in a less range by absence of maintenance, eg broken outside doors, damaged roofs etc. Energy consumption in dwelling houses with design indoor temperature and normal maintenance level usually is near to the design value or less up to 10%. In dwelling houses, in which energy consumption is defined as being of less design value, some energy saving measures are applied, eg temperature in spaces is lowered up to 16 °C, about half of balconies are glassed, electric stoves for cooking are installed as additional heat source. Such apartment buildings, as a rule, do not have premises of other destination. By such means near 40% of heat is saved. Article in Lithuanian. First Published Online: 26 Jul 2012